A mechanism that ensures non-selective cytoplasm degradation by autophagy - Tetsuya Kotani; Yuji Sakai; Hiromi Kirisako; Chika Kakuta; Soichiro Kakuta; Yoshinori Ohsumi; Hitoshi Nakatogawa (Nature Communications, 2023)
Abstract In autophagy, a membrane cisterna called the isolation membrane expands, bends, becomes spherical, and closes to sequester cytoplasmic constituents into the resulting double-membrane vesicle autophagosome for lysosomal/vacuolar degradation. Here, we discover a mechanism that allows the isolation membrane to expand with a large opening to ensure non-selective cytoplasm sequestration within the autophagosome. A sorting nexin complex that localizes to the opening edge of the isolation membrane plays a critical role in this process. Without the complex, the isolation membrane expands with a small opening that prevents the entry of particles larger than about 25 nm, including ribosomes and proteasomes, although autophagosomes of nearly normal size eventually form. This study sheds light on membrane morphogenesis during autophagosome formation and selectivity in autophagic degradation.